Le rapport ordinaire à l’héritage bâti de l’époque de la colonisation française en Algérie : L’exemple de l’hôtel de ville de Kherrata (Bejaia) - Idir Benaidja (L’Année du Maghreb)
The issue of heritagization does not only depend on the institutions and law, but also on society. This article deals with the relationship between the local population and the architectural legacy of the French colonization in a specific case: the city hall of a small Algerian city located in the North-East of the country: Kherrata (Bejaia). It aims to contribute to the scientific debate about the process of heritagization. How does the population relate to the town hall? How is their relationship to other colonial buildings? How are social representations of the colonial architecture constructed over time? This work provides some answers to these questions and seeks to open reflection on the ordinary relationship of populations to colonial buildings. The methodology combines architectural and urban knowledge of the city with a questionnaire designed to understand the representations that the population has of this built as a heritage object.